Definition of quality of life in patients with sequellae of mild traumatic brain injuries before and after neurometabolic therapy - Iakubenko, Iu. (Международный медицинский журнал, 2014)
The study involved 75 patients with sequellae of mild traumatic brain injuries. The neurometabolic therapy in the patients with sequellae of mild traumatic brain injuries was more effective in comparison with basic symptomatic therapy, since neurometabolic therapy influenced the processes of metabolism of brain, decreased its sensation to chronic hypoxia, which developed against a background of vegetative dystonia due to the injury and influence of the above therapy on the neurotransmitter system. The neurometabolic therapy in patients with sequellae of mild traumatic brain injuries improved the quality of life.